RSN - Rede Social de Notícias - Monteiro, Eduardo Rocha (2009)
Within the set of transformations from the evolution of the Internet, there is one that has nothing to do about processing and presenting information, but no less important than the other changes: the transformation of the behavior of the Internet User. If before it was a mere consumer of information, now he actively participates, evaluating and creating content in the web. This scenario has stimulated the development of new technologies to support the community on the web, which now enables a broad mechanism of interaction for many people, which promotes the formation of important virtual spaces with respect to the construction and socialization of knowledge. In this context, the virtual social networks stands out. Virtual social networks are virtual spaces that include a structure made by individuals and organizations connected by one or more types of interdependency, such as values, visions, ideas, friendship or business interests. This work conducted a study on the state of the art on virtual social networks and on the recommender systems, in order to create a virtual social network which enables content share by users, and a recommendation systemto direct relevant information for its users. Was also a study on the social news aggregators, that constitute a specific category of virtual social networks. The system RSN: Social Networking News was develop as the main product of this work. RSN adds features of social news aggregators to other characteristics of virtual social networks in order to build a virtual space with a high potential display of interesting news to its users.